Role of percolating melts in Antarctic subcontinental lithospheric mantle: New insights from Handler Ridge mantle xenoliths (northern Victoria Land, Antarctica) - Pelorosso, B.; Bonadiman, C.; Coltorti, Massimo; Melchiorre, Massimiliano; Giacomoni, Pier Paolo; Ntaflos, T.; Grégoire, Michel; Benoit, M. (Geological Society of America, 2017)
The petrology of anhydrous peridotite xenoliths hosted in the Cenozoic alkaline volcanic rocks from Handler Ridge (northern Victoria Land, Antarctica) provides new constraints on the characterization of the subcontinental lithospheric mantle beneath the West Antarctic Rift. For most samples, the temperature of equilibration was calculated on the basis of Fe/Mg partitioning among olivine, orthopyroxene, and spinel, at a pressure of 15 kbar. These results revealed a temperature of ∼1030 °C and fO2 ranging from -0.26 to +0.39 with respect to fayalite-magnetite-quartz buffer (δFMQ). Compared with other anhydrous and hydrated mantle xenolith suites occurring in northern and southern Victoria Land, these xenoliths represent the highest-temperature and most-oxidized conditions. On the basis of major-element modeling, we suggest that this portion of the mantle represents a residuum after 7%-18% partial melting. Geochemical and isotopic compositional evidence is indicative of significant metasomatism caused by an alkaline melt almost entirely overprinting the residual peridotite composition within a period of 102-103 yr. © 2017 The Geological Society of America. All rights reserved. Peer reviewed